2008
DOI: 10.1097/ta.0b013e31818234aa
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Vascular Shunts as Initial Treatment of Proximal Extremity Vascular Injuries During Combat Operations: The New Standard of Care at Echelon II Facilities?

Abstract: Complex combat injuries to proximal extremity vessels should be routinely shunted at forward-deployed Echelon II facilities as part of the resuscitative, damage control process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 15 publications
1
63
0
2
Order By: Relevance
“…Vascular damage control involves a truncated approach of early and rapid revascularization, most often with an interpostion shunt. 56,57 Early external fixation offers the added advantage of providing skeletal stability to protect temporary vascular shunts or definitive repairs. 58,59 Extremity damage control also involves débridement of grossly contaminated tissues and the liberal use of fasciotomies.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…Vascular damage control involves a truncated approach of early and rapid revascularization, most often with an interpostion shunt. 56,57 Early external fixation offers the added advantage of providing skeletal stability to protect temporary vascular shunts or definitive repairs. 58,59 Extremity damage control also involves débridement of grossly contaminated tissues and the liberal use of fasciotomies.…”
Section: Damage Control Resuscitationmentioning
confidence: 99%
“…, and the authors meticulously documented the time from shunt placement to casualty presentation at the level 3 surgical facilities in Baghdad or Balad, Iraq. These authors also validated the earlier experience of a US Navy forward surgical unit and concluded that complex combat injuries to proximal extremity vessels should be routinely shunted at forward-deployed Echelon II facilities as part of the resuscitative, damage control process [ 15 ].…”
Section: Operative Managementmentioning
confidence: 90%
“…While flow rates are lower than their arterial counterparts, the patency of venous shunts is comparable. [21][22][23] Successful use of vascular shunts in venous injuries has also been reported the civilian sector as Parry and colleagues have described 18 cases either to allow for orthopedic fixation or to control hemorrhage during a damage control operation. All venous shunts in their series were patent on reexploration at a mean 22 hours dwell time.…”
Section: Venous Shuntingmentioning
confidence: 94%
“…21 The favorable experience with the use of vascular shunts in this initial report was corroborated by subsequent series provided by other combat surgical teams. [22][23][24] Figures 17-2, A-C detail a case example in which a midsubclavian injury was initially treated at a forward surgical location with the insertion of an intraluminal shunt and subsequently was repaired with interposition graft at a higher level of care. Gifford and colleagues provided one of the only studies to characterize longer-term extremity outcomes following the use of temporary vascular shunts.…”
Section: Shunt Materialsmentioning
confidence: 99%